2016
DOI: 10.1007/s10995-016-1950-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptoms and Social Functioning Following Repair of Obstetric Fistula in a Low-Income Setting

Abstract: Objectives Obstetric fistula is a maternal injury that causes uncontrollable leaking of urine or stool, and most women who develop it live in poverty in low-income countries. Obstetric fistula is associated with high rates of stigma and psychological morbidity, but there is uncertainty about the impact of surgical treatment on psychological outcomes. The objective of this exploratory study was to examine changes in psychological symptoms following surgical fistula repair, discharge and reintegration home. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 29 publications
2
36
1
Order By: Relevance
“…They found it important to educate on the possibility that the repair might not be successful in resulting in complete dryness and to provide coping skills if this was the case. 21 A study in Malawi found similar rates of interest in future childbearing and reported that reintegration was relatively easy for these women. However, women continued to have difficulty in their lives relating to fertility and relationships.…”
Section: Discussionmentioning
confidence: 96%
“…They found it important to educate on the possibility that the repair might not be successful in resulting in complete dryness and to provide coping skills if this was the case. 21 A study in Malawi found similar rates of interest in future childbearing and reported that reintegration was relatively easy for these women. However, women continued to have difficulty in their lives relating to fertility and relationships.…”
Section: Discussionmentioning
confidence: 96%
“…This is in contrast to low‐income countries where VVF is consequent to obstructed second stage of labor in >95% of cases . Management of VVF varies, with no standardized treatment pathway.…”
Section: Introductionmentioning
confidence: 94%
“…2 The association of ureteral injuries with VVF is unknown, as there is a variability in the series, with reports ranging between 6 and 25% of cases. 3 However, preoperative diagnosis is essential for the planning of repair surgery. The article by Seth et al 4 presents a large series of 116 patients with VVF, emphasizing the incidence and management of these patients when there is an association of ureteral injury.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Unrepaired obstetric fistula can lead to a life of disability, poverty, and isolation . Not surprisingly, mental health assessment of women with obstetric fistula has demonstrated high rates of depression …”
Section: Introductionmentioning
confidence: 99%